(untitled) (Journal of Bio-Science, 2016)
Context: Streptomyces are potential sources for secondary metabolites possessing a variety of biological activities with antimicrobial activity, which is used for human and animal treatment. It is estimated these bacteria synthesize more than 7,000 metabolites. About 80% of these are made by members of the genus Streptomyces. Streptomyces spp. is known as producers of several bioactive metabolites which has antibiotic, antiparasitic, antitumor, insecticide, herbicide, etc. Objectives: Determine the antimicrobial activities of Streptomyces isolates and compare the efficacy of the antimicrobial activities of Streptomycetes with selected commercial antimicrobial agents. Materials and methods: Collection of samples and test organisms; physicochemical screening; antimicrobial assay (co-culture method); antibiotics sensitivity test (disc-diffusion assay). Result: Streptomyces griseoflavus, Streptomyces parvus and Streptomyces albidus were isolated from dry soil while Streptomyces vinaceus and Streptomyces globiosporus from moist-fresh soil and fish pond water used for cultivation of cat fish Clarias garienpinus respectively. Out of these five (5) isolates isolated, 3 isolates (60%) exhibited antibacterial activity against the following pathogenic, nosocomial organisms: Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus aureus, Candida spp, Aspergillus fumigatus, Aspergillus flavus, Aspergillus saprophyticus, and Trichoderma spp respectively. S. griseoflavus demonstrated antibacterial activity against K. pneumoniae, Trichoderma spp and Candida spp. S. albidus against S. typhi and A. fumigatus while S. parvus was inhibitory to S. aureus and A. fumigatus. The active isolates inhibited bacteria growth (0 to 39.33 mm). Commercial antimicrobials used also demonstrated inhibitory effects against the test pathogens. Conclusion: The garden soil of FUTA farm contains Streptomyces spp. with antibacterial and antifungal activities. J. bio-sci. 22: 21-29, 2014